Konsumsi sayuran hijau dengan kejadian anemia pada ibu hamil - Dessy Hermawan; Zaenal Abidin; Dwi Yanti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Consumption of dark green, leafy vegetables and maternal anemia during pregnancyBackground: The data base of the statistical bureau agency in Indonesia, the prevalence of maternal anemia during pregnancy is still relatively high and tends to increase where in 2013 in urban areas amounted to 36.4%, in rural areas 37.8% so that the average 37.1%. in 2018 it has increased significantly to an average of 48.9%. The incidence of maternal anemia during pregnancy in 12 public health centre (Puskesmas) in North Lampung was found a public health centre (Puskesmas) that was classified as still high in Semuli Raya public health centre (Puskesmas) (33.6%).Purpose: Knowing of consumption of dark green, leafy vegetables and maternal anemia during pregnancyMethod: A quantitative study with an analytical survey using the cross sectional study. The samples were 60 respondents and analysis of statistical tests used the chi-square test.Results: The consumption of dark green, leafy vegetables in 60 respondents, 29 respondents (48.3%) consumes vegetables every day, and 31 respondents (51.7%) has seldom consumes. Hemoglobin status in 60 respondents, 28 respondents ( 46.7%) had normal range of haemoglobin and 32 respondents (53.3%) had lower of haemoglobin . Statistical test results using chi square obtained p-value of 0.000.Conclusion: There was correlation of consumption of dark-green leafy vegetables in prevention of maternal anemia during pregnancy.Keywords: Consumption; Dark green, Leafy vegetables; Maternal anemia; During pregnancyPendahuluan: Data dari badan pusat statistik di Indonesia, prevalensi anemia pada ibu hamil tergolong masih tinggi dan cenderung meningkat dimana di tahun 2013 di perkotaan sebesar 36.4 %, di perdesaan 37.8% sehingga rerata 37.1%. di tahun 2018 telah naik secara signifikan menjadi rerata 48.9%. Kejadian anemia pada ibu hamil di 12 Puskesmas di Kabupaten Lampung Utara didapatkan ada puskesmas yang tergolong masih tinggi di Puskesmas Semuli Raya (33.6%).Tujuan: Diketahui hubungan konsumsi sayuran hijau dengan kejadian anemia pada ibu hamil.Metode: Jenis penelitian kuantitatif dengan rancangan survey analitik dengan menggunakan pendekatan cross sectional. Jumlah sampel sebanyak 60 orang dan analisis uji statistik menggunakan uji chi square.Hasil : Konsumsi makanan sayuran hijau pada 60 responden sebanyak 29 responden (48,3%) mengkonsumsi sayuran hijau setiap hari, dan sebanyak 31 responden (51,7%) jarang mengkonsumsi sayuran hijau setiap hari. Status hemoglobin pada 60 responden sebanyak 28 responden (46,7%) memiliki hb normal, dan sebanyak 32 responden (53,3%) memiliki hb rendah. Hasil uji statistik menggunakan chi square didapat nilai p-value 0.000 < 0,05.Simpulan : Ada hubungan konsumsi sayuran hijau dengan kejadian anemia pada ibu hamil.